2016
DOI: 10.4049/jimmunol.1600940
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbial Membership Modulates CD4 T Cell Reconstitution and Function after Sepsis

Abstract: Transient lymphopenia is one hallmark of sepsis, and emergent data indicates the CD4 T cell compartment in sepsis survivors is numerically and functionally altered (when examined at the Ag-specific level) compared to non-septic controls. Previous data from our laboratory demonstrated Ag-independent, lymphopenia-induced homeostatic proliferation to be a contributing mechanism by which CD4 T cells numerically recover in sepsis survivors. However, we reasoned it is also formally possible that some CD4 T cells res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…Neither of these studies examined any elements of the immunophenotype. An elegant study by the Griffith group compared Jax mice to mice from a different vendor following CLP, taking advantage of the fact that these mice differed in whether they had segmented filamentous bacteria (SFB) (34). SFB-specific CD4 + T cells underwent antigen-driven proliferation following sepsis in mice that contained this normal gut microbe but not in genetically identical mice that lacked the microbe.…”
Section: Discussionmentioning
confidence: 99%
“…Neither of these studies examined any elements of the immunophenotype. An elegant study by the Griffith group compared Jax mice to mice from a different vendor following CLP, taking advantage of the fact that these mice differed in whether they had segmented filamentous bacteria (SFB) (34). SFB-specific CD4 + T cells underwent antigen-driven proliferation following sepsis in mice that contained this normal gut microbe but not in genetically identical mice that lacked the microbe.…”
Section: Discussionmentioning
confidence: 99%
“…Specific bacteria play a role in affecting or regulating the immune system (87,88). The composition changes of the gut microbiota have recently been observed in several forms of immunodeficiency in mice (92)(93)(94). Investigation of the population structure and taxonomic or functional features of the microbiota may unfold how gut bacteria regulate the immune system both in patients with PID and healthy individuals.…”
Section: Metagenomicsmentioning
confidence: 99%
“…It has been widely reported that TLRs serve important roles in the progression of lung diseases (26). Microbe-derived LPS is suggested to be a major element involved in the development of sepsis (28). In general, LPS triggers inflammatory responses by activating TLRs, which then recruit neutrophils to the inflammatory site (25,29).…”
Section: Discussionmentioning
confidence: 99%